e-lab Remote Laboratory Demonstration - Neto, R. B.; Fernandes, H. (International Journal of Online and Biomedical Engineering (iJOE), 2013)
e-lab is a remote laboratory infrastructure,powered by a software framework designed for distributeddata collection, that allows to perform experiments andretrieve data from a remote apparatus. In thisdemonstration we will present the e-lab interface propertiesand its modus operandi, giving as well some topics ofcomplimentary software use for data interpretation andanalysis. An overview of e-labâ??s technical specifications willalso be presented.